E-wallet using NFC mobile application development - Chong, Yao En (2023)
There are many payment methods that exist in this advanced technology era, so payment is no longer limited to cash payment, card payment and so on. It could be easy to be replaced by a technology payment method. People also no longer require bringing along their payment card or cash to make any transaction since a new technology NFC can be utilised to develop this activity.